Analisis Jaringan Irigasi pada Daerah Irigasi Waduk Tenggor Desa Tenggor Kecamatan Balongpanggang Gresik: Analysis of Irrigation Network in the Tenggor Reservoir Irrigation Area, Tenggor Village, Balongpanggang Subdistrict, Gresik - Yuli Hariyanti; Dewi Nusantara, Danayanti Azmi (Jurnal Rekayasa Infrastruktur HEXAGON, 2023)
The irrigation system at Tenggor Reservoir in Tenggor Village, Balongpanggang, Gresik cannot be used to irrigate rice crops. Water volume frequently decreases and is not used to its fullest potential. Therefore, in order to correctly manage water resource management, it is required to analyze the irrigation network in an attempt to restore the irrigation network's functionality. The FJ Mock method for calculating the mainstay discharge gave the highest 80% value of 1,597 m3/s with the greatest discharge requirement of 1,456 m3/s. The overall reservoir capacity was calculated using reservoir storage. The reservoir's overall storage capacity was found to be 219345 m3, as well as its effective capacity of 186443 m3 and its dead capacity of 32902 m3. The NFR of Tenggor Irrigation Area with the paddy's planting pattern is 1.083 lt/dt/ha. The total capacity needed for irrigate is 287067 m3 whereas the availability of an effective capacity is 186443 m3. So, with the availability of 70% of the effective capacity, it can supply the irrigation areas of 860 ha with twice of planting patterns. The study's findings include five different channel dimensions with various water levels. Type 1 for tertiary channels with B and H dimensions of 0.50 meters each. For secondary channels with various B sizes in order, type 2, type 3, and type 4: B = 0.50, 0.70, 0.80, and the same H sizes are 1.00 meters, respectively. Type 5 with B = 1.30 m and H = 1.50 m for the main channel.